Mathematical achievement ability in public primary schools of Zimbabwe - Musemburi, Loreen (Papanda Publisher, 2025)
Mathematical achievement ability often reflects the capacity of learners to grasp and apply foundational mathematical concepts. Ability to achieve in mathematics was evaluated using Wide Range Achievement Test - Expanded Edition (WRAT-Expanded) psychometric test. This comprehensive version assesses academic skills such as reading, spelling and arithmetic across a broader range of abilities and age groups. A sample of Grade 6 learners (n= 66) who were enrolled into the Avondale primary school and (n= 4) teachers, who were directly responsible for teaching the selected learners, were assessed and interviewed respectively as part of the study. The mixed approach design was used in this study and participants were selected using convenience sampling. The study was structured based on the cognitive and social constructivism theories. Findings indicated that mathematical achievement ability is in the average range, with the girls showing higher mathematical cognitive abilities as compared to boys. It emerged that the mathematical achievement ability of learners aligns with comprehension and grasping of mathematical concepts, attitude towards mathematics, and learner`s progress in mathematics. The findings also showed that performance in mathematics can be affected by learners’ beliefs that it is a difficult subject, poor comprehension of mathematical terms, motivation of the teachers to teach mathematics, and lack of adequate resources to teach the subject. The study recommends teachers to be provided with in-service training programmes and refresher courses. These will equip them to respond to attitudes, and gender differences in mathematics, ensuring inclusive and equitable learning opportunities. Findings from this study, can help curriculum design and pedagogy to be learner-centered, addressing not only cognitive skills but also emotional and motivational aspects of learning mathematics.